How Frequent does Bow and Arrow Sign Locate Ileocecal Valve during Colonoscopy? - Akere, Adegboyega; Edries, Tejan Ahmad (Journal of Digestive Endoscopy, 2018)
Aim: Two major ways to locate the ileocecal valve (ICV) are to look for a thickening or bulge on the ileocecal fold, and the other is the “bow and arrow” method or the “appendix trick”. The aim of this study was to determine the accuracy of “bow and arrow” method to locate the ICV during colonoscopy. Patients and Methods: Colonoscopy was performed with the patients in the left lateral position. After cecal intubation had been confirmed, the appendiceal opening was identified, with the curve serving as the bow, an imaginary arrow was placed across the curve toward the appendix lumen. The tip of the imaginary arrow was then followed to confirm if it correlated to the location of the ICV. Results: The “bow and arrow” accurately located the ICV in 105 (76.6%) patients, but failed in 32 (23.4%) patients. The mean age (56.2 ± 13.1 years) of the patients in whom the “bow and arrow” located the ICV was lower than that (62.7 ± 0.9 years) of the patients in whom it failed to locate the ICV. Males, 58 (71.6%) had positive “bow and arrow”, while this was observed in 47 (83.9%) females. It correctly located the ICV in 73 (53.3%) of those with thin‑lip ICV, 20 (14.6%) of those with volcanic type, and 12 (8.8%) of those with double bulge ICV. Conclusion: The bow and arrow sign could not locate the ICV in all cases in our practice and so where it failed, alternative method should be employed to locate the ICV.
Keywords: Appendiceal orifice; bow and arrow; colonoscopy; ileocecal valve